2009
DOI: 10.1111/j.1439-0418.2008.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Hessian fly (Diptera: Cecidomyiidae) in the Fertile Crescent

Abstract: The Hessian fly, Mayetiola destructor (Say), is an important insect pest of wheat (Triticum spp.) in North Africa, North America, southern Europe and northern Kazakhstan. Both wheat and this pest are believed to have originated from West Asia in the Fertile Crescent. The virulence of a Hessian fly population from Syria against a set of cultivars carrying different resistance genes, in addition to other effective sources with unknown genes, was determined in the field and laboratory at the International Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…The Near East is the center of origin of wheat and its ancestors (Salamini et al 2002, Devos 2010 and also seems to be the center of origin of the Hessian ßy (Barnes 1956). Today this region contains some of the worldÕs most virulent Hessian ßy populations (El Bousshini et al 2008) and also contains many host and nonhost grass species. If H genes have no costs, they may have played a role in the evolution of durable nonhost resistance (Heath 2000), evidence for this coming from nonhost grasses that are closely related to host grasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Near East is the center of origin of wheat and its ancestors (Salamini et al 2002, Devos 2010 and also seems to be the center of origin of the Hessian ßy (Barnes 1956). Today this region contains some of the worldÕs most virulent Hessian ßy populations (El Bousshini et al 2008) and also contains many host and nonhost grass species. If H genes have no costs, they may have played a role in the evolution of durable nonhost resistance (Heath 2000), evidence for this coming from nonhost grasses that are closely related to host grasses.…”
Section: Discussionmentioning
confidence: 99%
“…For highly effective resistance genes that have not yet been deployed, deployment through stacking is probably a better use of the gene than serial deployment (Gould 1986(Gould , 1998. One such gene is H26, which is effective against all known Hessian ßy populations, including the worldÕs most virulent populations (El Bousshini et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from North Africa indicated that H11 and H13 genes were resistant to Tunisian Hessian fly (Bouktila et al, 2005) Bouhssini et al, 1999;Lhaloui et al, 2000). In West Asia, two resistance genes, H25 and H26, have recently been reported to be effective against Hessian fly populations from Syria (El Bouhssini et al, 2009). Besides, a recent virulence analysis reported that H13, H21, H25, H26 and Hdic were the most effective genes against three Hessian fly populations, namely Texas, Oklahoma and Kansas, in USA .…”
Section: Resultsmentioning
confidence: 99%
“…But, here there is question: Is the evolution of Hessian ßy virulence driven solely by H gene deployment in agriculture or does it also occur outside of agriculture? Support for the latter hypothesis comes from the biotype composition of the worldÕs Hessian ßy populations: populations in regions with no history of de- ploying H genes often have high frequencies of virulence (Harris 1993;Ratcliffe et al 1994Ratcliffe et al , 2000El Bouhssini et al 2008;Chen et al 2009). Explanations for these high virulence frequencies are 1) unintended deployment of H genes in wheat cultivars resulting in unknown exposure of Hessian ßy populations; or 2) selection of avirulence genes via H genes present in wild hosts, with this creating preadapted populations that survive when the H gene is deployed in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Fitness costs have not been investigated for the Hessian ßy, Mayetiola destructor (Say) (Diptera: Ce-cidomyiidae), managed by gene-for-gene plant resistance mediated by H genes (Barnes 1956, Gould 1986, Ratcliffe and Hatchett 1997, Berzonsky et al 2003, El Bouhssini et al 2008, Porter et al 2009). The Hessian ßy is one of the worldÕs most important pests of wheat (Triticum aestivum L.).…”
mentioning
confidence: 99%